Native and Novel Language Prosodic Sensitivity in English‐Speaking Children with and without Dyslexia. (26th February 2013) - Anderson, Alida; Lin, Candise Y.; Wang, Min
<x xml:space="preserve">Abstract</x> Children with reading disability and normal reading development were compared in their ability to discriminate native (English) and novel language (Mandarin) from nonlinguistic sounds. Children's preference for native versus novel language sounds and for disyllables containing dominant trochaic versus non‐dominant iambic stress patterns was also assessed. Participants included second and third grade monolingual native English speakers with reading disability (N = 18) and normal reading development (N = 18). Children selected from pairs of novel, native, and nonlinguistic sounds that was more like language. Both groups discriminated disyllabic linguistic sounds (native and novel) from nonlinguistic sounds. Both groups showed preference for the dominant English trochaic stress pattern over the non‐dominant iambic stress pattern. Implications for development of prosodic sensitivity in relation to reading skills and future research are discussed. Copyright © 2013 John Wiley & Sons, Ltd.